The Level of Knowledge of Secondary School Students in Penang About HIV/AIDS: Pre and Post Intervention - Bahrin, Farhana Kamarul; Azman, Azlinda; Zainol, Intan Nooraini Haji; Yusof, Masarah Mohamad; Shaed, Maslina Mohammed (International Journal of Asian Social Science, 2018)
HIV and AIDS is no stranger to the world population where more than 70 million people have been infected with HIV (World Health Organization, 2016). HIV/AIDS education for young people plays an important role in ending the AIDS epidemic globally. It is reported that Malaysians are still lacking of knowledge about HIV/AIDS, especially the cause of HIV and AIDS. The Ministry of Health Malaysia (2017) has reported that nearly 85% of HIV infections in 2016 are due to sexual activity. For the year 2016, there were 103 cases of new HIV/AIDS infections involving the age of 13 years - 19 years (Ministry of Health Malaysia, 2017) were reported. This quantitative study involved 600 students aged 15 years old, 16 years old and 17 years old in Penang. Study respondents have participated in three sessions of data collection phases, involving pre-test phase, intervention phase and post-test phase. Data collected was analyzed using SPSS 22.0 software. The study findings have indicated that the hypothesis test for knowledge has shown some changes in the level of knowledge of the respondents after receiving information on HIV/AIDS (t = -46.561, sig. <0.05 and post knowledge’s mean was 13.813 is higher than pre knowledge’s mean, 8.715). The study findings concluded that there is a strong need to have an informative and interacting Module on HIV/AIDS to be used in secondary schools in Malaysia as a form of intervention. This is to ensure that adolescents able to acquire basic and sufficient knowledge about HIV/AIDS.